A review of a decade of Rugby Union injury epidemiology: 2007-2017 - Viviers, P. L.; Viljoen, J. T.; Derman, P. W. (Sports Health: A Multidisciplinary Approach, 2018)
Context: Rugby union is the most widely played team collision sport globally. As with other contact sports, there is substantial risk of injury. To date, the majority of studies on injury epidemiology have focused on elite male cohorts, which inherently prevents extrapolation of research findings to other groups within the player continuum. This review aims to describe emerging injury trends across the spectrum of various rugby union subpopulations and to highlight gaps that may influence future injury prevention tactics. Evidence Acquisition: Relevant articles published from 2007 to 2017 were obtained by searching MEDLINE, PubMed, and SPORT Discus. Studies on 15-a-side rugby union, implemented according to the 2007 consensus statement on injury definitions and data collection procedures for injuries in rugby union, were used. Study Design: Clinical review. Level of Evidence: Level 3. Results: Match injuries occur more frequently than training injuries. Injury rates increase consistently according to age and level of play. Severity of injury often is greater among lower levels of the game, and sex-specific differences relating to injury patterns and incidence rates exist. Conclusion: To date, a paucity of injury surveillance data exists for women and players of both sexes at all levels of community rugby union. Furthermore, the incidence of injuries and illnesses are poorly reported in epidemiological studies. Despite methodological differences, injury trends remain consistent throughout all levels of play.